2016
DOI: 10.1097/coc.0000000000000045
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Target-guided Personalized Chemotherapy in First-line Metastatic Colorectal Cancer

Abstract: Real-time target-guided personalized first-line treatment of patients with advanced CRC is feasible but, with the approached used, did not result in a clear improvement in PFS to warrant phase III testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…With so many potential targets for therapy, personalized treatments with existing drugs would be expected to show improved results. Early trials of personalized therapy based on mutation status of KRAS, BRAF, PI3KCA, and expression of Topo-I, ERCC1, TS, and TP did not show any improvement in PFS [Cubillo et al 2014]. However, some authors have proposed using KRAS, BRAF, PI3KCA, and PTEN mutation status as a signature to guide therapy [Bardelli and Siena, 2010;Sartore-Bianchi et al 2009].…”
Section: Discussionmentioning
confidence: 99%
“…With so many potential targets for therapy, personalized treatments with existing drugs would be expected to show improved results. Early trials of personalized therapy based on mutation status of KRAS, BRAF, PI3KCA, and expression of Topo-I, ERCC1, TS, and TP did not show any improvement in PFS [Cubillo et al 2014]. However, some authors have proposed using KRAS, BRAF, PI3KCA, and PTEN mutation status as a signature to guide therapy [Bardelli and Siena, 2010;Sartore-Bianchi et al 2009].…”
Section: Discussionmentioning
confidence: 99%
“…In view of these results, more efforts are needed to validate them in prospective clinical trials. Two examples can be found in the works of Kim do and Cubillo (62,63); in the former, patients were randomized to receive either FOLFOX combination or a treatment according to genotypes for certain polymorphisms. In this group, FOLFOX was selected on the basis of XPD-751, GSTP-1-105, and XRCC1-399 genotypes.…”
Section: The Glutathione Systemmentioning
confidence: 99%
“…Indeed, research on personalized treatment of mCRC patients beyond the confirmed negative predictive role of RAS mutations for anti-epidermal growth factor receptor (EGFR) antibodies is far from conclusive [10]. …”
Section: Introductionmentioning
confidence: 99%